Effect of Oxide Treatment at the Mycrocrystalline Tunnel Junction of a-Si:H/a-Si:H Tandem Cells - Rath, J.K. (2000)
The electrical transport taking place in the μc-Si tunnel recombination junction (TRJ) of a-Si:H/a-Si:H tandem solar cells and the role of CO2 plasma oxidation performed between microcrystalline layers is investigated in this paper with the computer code AMPS. Oxidized interfaces were modelled as simple highly defective intrinsic μc-Si layers. Two different tunnel junction structures are studied in this paper: (a) (n)μc-Si/oxide/(p)μc-Si and (b) (n)μc-Si/(i)μc-Si/(p)μc-Si. In the last configuration the oxide interface is removed and replaced by a thin defective (i) μc-Si layer. Both tunnel junctions have comparable theoretical and experimental tandem solar cell efficiencies which indirectly proves that our modelling assumption for oxidised interfaces is correct. A-Si:H/a-Si:H tandem solar cell efficiencies depend on the thickness of the intrinsic layer introduced in the tunnel junction. The optimisation of this thickness provides a more controlled way of achieving greater efficiencies in a-Si:H/a-Si:H tandem solar cells.